2004
DOI: 10.1111/j.1600-0501.2004.01085.x
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular overdentures supported by two or four endosseous implants

Abstract: There is no difference in clinical and radiographical state of patients treated with an overdenture on two or four implants during a 5-year evaluation period. Patients of both groups were as satisfied with their overdentures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
127
6
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(155 citation statements)
references
References 20 publications
17
127
6
5
Order By: Relevance
“…[6][7][8] Bar-clip and O-ring overdenture abutments are the most common types, and they are classified as resilient systems. 9,10 These retentive mechanisms attached to implants transmit stress to the bone differently than natural teeth supported by periodontal ligaments. 5,11,12 If the incident force on the implant exceeds the physiological limit, it can result in overload, with consequent bone microfractures that can heal with nonmineralized connective tissue or lost tissue, because the implants are not prepared to support excessive force.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Bar-clip and O-ring overdenture abutments are the most common types, and they are classified as resilient systems. 9,10 These retentive mechanisms attached to implants transmit stress to the bone differently than natural teeth supported by periodontal ligaments. 5,11,12 If the incident force on the implant exceeds the physiological limit, it can result in overload, with consequent bone microfractures that can heal with nonmineralized connective tissue or lost tissue, because the implants are not prepared to support excessive force.…”
Section: Introductionmentioning
confidence: 99%
“…In group one the patients received two IMZ implants each and in group two the patients received four implants each. There were no significant differences with regard to the clinical and radiological parameters [61].…”
Section: Studies With Comparison Of Two Versus Four Implants In the Ementioning
confidence: 73%
“…Only a few randomized prospective studies with longer observation periods have been carried out to date. There is comparison of implant-supported overdentures involving two versus four implants in only four studies [59][60][61][62]. There have been just as few studies that have investigated the influence of the opposing jaw on the treatment success of the mandible with implants.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have proved that the number of implant used to retain an overdenture does not influence the treatment outcomes. 18 Systematic reviews and randomized clinical trials have also concluded that two implant supported overdenture should be the minimum gold standard treatment for edentulous patients. 19,20 We have also used the well accepted, scientifically proven and cost effective concept of two implants in the inter-foramina region of the mandible to support an overdenture.…”
Section: S351mentioning
confidence: 99%